Corporate social performance and financial performance relationship in banks: sub-industry and cross-cultural perspective - Daszyńska-Żygadło, Karolina; Słoński, Tomasz; Dziadkowiec, Anna (Journal of Business Economics and Management, 2021)
The aim of the paper is to reveal how corporate social performance (CSP) affects market value and earnings capabilities of companies from banking industry: Banking Services and Investment Banking & Investment Services sub-industries in particular. For Banking Services, the research was extended to a link between corporate social performance and corporate financial performance (CSP-CFP) by classifying institutions into clusters based on a type of culture which dominates in a bank’s country of origin. Regression analysis was run on a unique dataset, which comprehensively captures the contextuality of CSP, measured with corporate governance, environmental and social characteristics. This research uses Refinitiv database of ESG Scores as CSP proxy for banks from all over the world in the period of 2009–2016. The results confirm that environmental performance and social performance have negative impact on CFP in banks and partly confirmed that governance performance has a positive impact on their CFP.  This research proves that banks’ CSP performance and the CSP-CFP relationship differs with regard to the type of bank operations as well as the associated culture. This is an important conclusion for investors seeking to increase value of their holdings and bank management who wants to foster bank’s profitability through CSP-related decisions.First published online 28 December 2020